Full Activation Profiles and Integrity of Corticospinal Pathways in Adults With Bilateral Spastic Cerebral Palsy. (January 2019) - Condliffe, Elizabeth G.; Jeffery, Dean T.; Emery, Derek J.; Treit, Sarah; Beaulieu, Christian; Gorassini, Monica A.
Background . Dysfunction of corticospinal pathways has been implicated in motor impairments in people with bilateral spastic cerebral palsy (CP). While structural damage to corticospinal pathways in people with CP is known, its impact on the activation of these pathways is not. Objective . To provide the first, complete activation profile of corticospinal pathways in adults with CP using a full range of transcranial magnetic stimulation (TMS) intensities and voluntary contractions. Methods . TMS targeted the soleus muscle of 16 adults with bilateral spastic CP and 15 neurologically intact (NI) control participants. Activation profiles were generated using motor-evoked potentials (MEPs) produced by varying both stimulation intensity and degree of voluntary muscle activity. Anatomical integrity of corticospinal pathways was also measured with diffusion tractography. Results . Participants with CP had smaller MEPs produced by TMS at 1.2× active motor threshold during submaximal (20%) muscle activity and smaller maximal MEPs produced under any combination of stimulation intensity and voluntary muscle activity. At a fixed stimulation intensity, increasing voluntary muscle activity facilitated MEP amplitudes to a lesser degree in the participants with CP. Consistent differences in diffusion tractography suggested structural abnormalities in the corticospinal pathways of participants with CP that correlated with maximal MEPs. Conclusion . People with bilateral spastic CP have impaired activation of low and high-threshold corticospinal pathways to soleus motoneurons by TMS and reduced facilitation by voluntary activity that may be associated with structural damage to these pathways. These impairments likely contribute to impaired voluntary movement.